Effects of tanniferous oak leaves (quercus hartwissiana) on some haematological parameters in lambs - Metehan Uzun; Feyyaz Önder; Metin Çenesiz; Mehmet Kaya; Sedat Yıldız (Eurasian Journal of Veterinary Sciences)
Aim of this study was to investigate whether feeding tanniniferous oak leaves (Quercus hartwissiana) for two months results in anaemia in lambs. For that purpose, 42 Tuj ewe lambs (&-9-month-oW) were used and the lambs were randomly allocated to one ol seven treatment groups (n = 6) as follows: control group, 0g leaf 0g PEG (polyethylene glycol, for binding tannins), group 1; 185 g leaf + O9 PEG, group 2; 185 g leaf + 10g PEG, group 3; 185 g leaf + 20g PEG, group 4; 370 g leaf + 0g PEG, group 5; 370 g leaf + 20g PEG, group 6; 370 g leaf + 40g PEG. All groups were given 272 g concentrate and varying amounts of hay, such that the amount of leaf plus to hay was equal to $45 g. The lambs were fed in individual metabolism cages twice daily at 08.00 and 16.00 h and had access to water at all times. Blood samples were collected at the end of the experiment (Day 60) and red blood cell count, haemoglobin concentration, haematocrit values, mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration and maximum and minimum osmotic haemolysis values were determined. Groups did not differ significantly in terms of the parameters measured. In conclusion, contrary to the reports related to other quercus species, in the current study, feeding Quercus hartwissiana lor two months did not result in anaemia in lambs.